Addressing foodborne threats to health : policies, practices, and global coordination (National Academies Press, 2006)
"In December 2004, at a press conference called to announce his departure as Secretary of the Department of Health and Human Services (DHHS), Tommy Thompson raised both concern and controversy when he remarked that he could not understand why terrorists had not yet attacked our food supply "because it is so easy to do." Three days later, the Food and Drug Administration (FDA) announced the last in a series of four food safeguards mandated under the Biopreparedness Act of 2002. Although these provisions improve the FDA's ability to intercept and track the origins of food that is suspected to pose a threat to health, they cannot prevent contamination. Biological and chemical agents can be--and have been--introduced, both accidentally and deliberately, at many vulnerable points along the farm-to-table food chain. Foodborne agents have been estimated to cause approximately 76 million illnesses, 325,000 hospitalizations, and 5,200 deaths in the United States each year. More than 250 different foodborne diseases, including both infections and poisonings, have been described, according to the CDC. The U.S. Department of Agriculture (USDA) estimates costs associated with medical expenses and losses in productivity due to missed work and premature deaths from five major types of foodborne illnesses (Campylobacter, Escherichia coli O157:H7, Shiga toxinproducing strains of E. coli, Listeria monocytogenes, and Salmonella) at $6.9 billion annually. This figure likely represents the tip of the iceberg, as it does not account for the broad spectrum of foodborne illnesses or for their wide-ranging repercussions for consumers, government, and the food industry. The potential impact on human health of deliberate adulteration of food can be estimated by extrapolation from the many documented examples of unintentional outbreaks of foodborne disease, some of which have sickened hundreds of thousands of people and killed hundreds. Given the wide variety of potential chemical and biological adulterants that can be introduced at many vulnerable points along the food supply continuum, contaminating food is perhaps one of the easiest means to intentionally distribute these agents. Although the many possibilities for foodborne bioterrorism cannot be specifically prevented, strategic preparations for surveillance, diagnosis, outbreak investigation, and medical response could mitigate foodborne threats of any origin. To examine issues critical to the protection of the nation's food supply, the Institute of Medicine's Forum on Microbial Threats hosted a public workshop on October 25 and 26, 2005, in Washington, D.C. The presentations and discussions of the workshop were structured to explore the existing knowledge and unanswered questions indicated by (but not limited to) the following topics: The globalization of the U.S. food supply; The spectrum of microbial threats to food; Case studies of food threats; The organization of food safety systems; Costs and benefits of reporting foodborne threats: the case of bovine spongiform encelphalopathy (BSE); Surveillance for foodborne illness."--Excerpted from Preface.